Association study of hypertension susceptibility genes ITGA9, MOV10, and CACNB2 with preeclampsia in Chinese Han population. (12th December 2022) - Xin, Qian; Xin, Gang; Li, Li; Sun, Wenjuan; Jiang, Wen; Wang, Jue; Luan, Yun; Zhang, Ying; Cheng, Ling; Duan, Shuhong; Hong, Fanzhen; Ji, Qinghong; et al.
Abstract: Objective: Preeclampsia (PE) is a disorder that occurs during the pregnancy and could affect the maternal and perinatal mortality as well as morbidity. The aim of our study is to investigate the associations between the hypertension susceptibility genes ITGA9, MOV10 and CACNB2 with PE in Chinese Han population. Methods: A case–control study including 178 PE patients and 202 healthy controls was conducted to assess the associations between three loci ( ITGA9 rs155524, MOV10 rs2932538 and CACNB2 rs4373814) and PE. The TaqMan probe assay was applied for genotyping in our study. Quantitative real-time PCR was performed to detect the mRNA expression levels of ITGA9, MOV10 and CACNB2. ELISA was carried out to detect the concentration of serum sFlt-1 or PLGF. Results: Our study detected no significant differences in allelic frequencies of three SNPs between PE patients and healthy controls. In the genetic model, the results showed that the patients with ITGA9 rs155524 GA or AA genotypes had a higher risk of PE development compared to those with GG genotype in codominant model. And PE patients had a higher frequency of GA + AA genotypes based on the dominant model. Subgroup analysis showed ITGA9 rs155524 was associated with early-onset PE but not with late-onset PE. No association was observed between MOV10 and CACNB2 with PE in any genetic model and subgroup analysis. Quantitative real-time PCR results showed that ITGA9 mRNA expression level was apparently increased in the placental tissues of PE patients. In addition, ITGA9 expression levels of GA + AA subjects were apparently higher than that in the genotype GG of placental tissues. sFlt-1/PLGF ratio was higher in GA + AA subjects than that in GG subjects. Regression analysis revealed that ratio of sFlt-1/PLGF was positively correlated with ITGA9 mRNA expression level. Conclusion: This study has identified ITGA9 is a promising candidate susceptibility gene for early-onset PE. Our findings demonstrated that the high expression of ITGA9 might be associated with an increased risk of PE.